Orthostatic Hypotension and Concomitant Paraneoplastic Syndromes: A Case Report - Bharati Dev; Ashwin Varkey; Hrede Afsana (European Medical Journal)
This case study discusses the incidence of a paraneoplastic autonomic neuropathy in an elderly male who had an otherwise negative work-up for their aetiology of orthostatic hypotension. This case illustrates the importance of trying to correctly identify the aetiology of orthostatic hypotension, which is often overlooked, and frequently diagnosed as idiopathic. Orthostatic hypotension is most prevalent in elderly populations and can be debilitating, leading to a higher incidence of falls and trauma. Thus, it is important to obtain further work-up when traditional treatments are ineffective. In patients with new and insidious onset of orthostatic hypotension, previous history of malignancy, and possible symptoms consistent with ongoing malignancy, it is imperative to consider paraneoplastic autonomic neuropathy as a potential cause of orthostatic hypotension.